The Effect of Art Therapy-Based Training on Auditory Processing Speed, Visual Processing Speed, and Working Memory and General Cognition of Multiple Sclerosis Patients (MS - Rezvaneh Qorbani Ranjbarzade; Navid Khalesi; Sanaz Dehghan Marvasti (پژوهش‌های کاربردی روانشناختی)
The purpose of this research was to study the effect of art therapy-based training on auditory processing speed-working memory, visual processing speed-working memory and general cognition of multiple sclerosis (MS) patients. The research methodology consisted of a semi-experimental clinical trial and a single-group pre-test-post-test design with a control group. The population under investigation consisted of 319 patients who were referred to the special diseases clinic of Ali Ibn Abitaleb Hospital in Rafsanjan County, Kerman Province, in 2017. The entrance and exit criteria were carefully considered when selecting the sample of 40 female patients. The Paced Auditory Serial-Addition Test (PASAT), Symbol Digit Modalities Test (SDMT), and Mini Mental State Examination (MMSE) were the research instruments. The experimental group’s classes were conducted in 14 sessions (45 minutes each) two times a week, while the control group’s classes were conducted in 14 sessions two times a week. Wilcoxon and univariate analysis of covariance were implemented in conjunction with SPSS version 20 software for data analysis. According to the findings, art therapy-based training enhances the speed of auditory processing-working memory, visual processing-working memory, and general cognition. Art therapy-based training sessions account for 21% of the variance in general cognition. It can be inferred that the auditory processing speed-working memory, visual processing speed-working memory, and general cognition of MS patients can be enhanced through art therapy-based education. It is recommended that psychology clinics implement art therapy-based training as a rehabilitation treatment.